Pengaruh Harga, Keanekaragaman Produk Dan Minat Beli Terhadap Keputusan Pembelian Produk Fashion Pada Toko Amie Metro - Nasikah, Durotun; Imantoro, Jati; Eliyani, Eliyani (Universitas Muhammadiyah Metro, 2023)
ABSTRACT Due to the large number of similar businesses, the business competition between these businesses is getting tougher where several factors that become competitive include prices, product diversity and the ability to create consumer buying interest. The main problem of this study aims to determine the effect of price, product diversity, and buying interest on purchasing decisions for fashion products at Amie Stores Metro. The research design is quantitative research or verification research. The method used in this research is price, product diversity, wants and needs, purchasing decisions and lifestyle. The population and sample of the study were students of the Management Study Program, Faculty of Economics and Business, University of Muhammadiyah Metro Batch 2018 with the number of samples taken as many as 68 students. Data collection techniques using questionnaires. The analytical tool used is data quality analysis and multiple linear regression with the SPSS program. The results showed that the price had no effect on consumptive behavior. Product diversity, and partial desire have a positive and significant effect on consumptive behavior. improve student purchasing decisions. Price, product diversity, and desire simultaneously have a positive and significant influence on consumptive behavior. Lifestyle moderates or increases the influence of price, product diversity, and desirability on consumer behavior.